Turtle Creek Chorale - Seeling, Timothy; Spencer, Antoine; Turtle Creek Chorale (Cave Springs, AR : ViaMedia Productions, Inc., 2005)
Presentaciones de distintos grupos corales durante la National Convention celebrada en Los Angeles, California entre el 2 y 5 de febrero del 2005
Contenido: The last words of David / Randall Thompson -- The vagabond / Ralph Vaughan Williams -- The language of angels / James Granville Eakin -- The shortest ballad in the world / Eric Lane Barnes -- How sweet the moonlight / Eric Helmuth -- The quest unending / Joseph Martin -- Solfeggio / Arvo Pärt
2005 National Convention
Keywords: MUSICA VOCAL; COROS (VOCES MASCULINAS); CONCIERTOS